In the Horizon of the Game with the Other - Antoniou, Klitsa (My University, 2026)
Klitsa Antoniou: In the Horizon of the Game with the Other, The Monagri Centre for Contemporary Art, Text: Jane Burton, Costa S.Theocharides. The Monagri Foundation, Cyprus 1999